Transition in Occupations of Refugees During Resettlement - Karen McCarthy; Jacqueline-Elizabeth Cantrell; Jennifer Daine; Kimberley Keegan Banuelos; Adam Chan (Scholarworks @ WMU, 2020)
Background: Human displacement is a social problem that has occupational implications. There is a significant gap in the research focusing on the refugee experience and the impact of this experience on their occupations as they transition to living in the US. This study seeks to capture the experience of refugees and the impact of this transition to the US on a broad array of occupations. Method: This research is a qualitative study. Data was collected through semi-structured interviews with two participants who have legal status as refugees living in the US. Results: Thematic analysis generated three themes: (a) contextual barriers to occupation, (b) belonging, and (c) adaptation. Refugees experienced a variety of contextual barriers, both systemic and socio-cultural, that impacted their ability to engage in meaningful occupation leading to a lack of belonging. Refugees adapted to these barriers by adapting their occupations. In addition, the researchers found social networks to be important for positive occupational engagement throughout country transition. Conclusion: This research adds to occupational science literature regarding the occupational impact of the refugee experience, as well as supporting occupational therapists to address issues of occupational deprivation with refugee populations.